Ecosystem restoration in Nepal: Needs and initiatives - Stahl, P.D.; Sapkota, R.P. (Nepal Journal of Environmental Science, 2014)
Nepal, situated in the Central Himalaya, occupies a total area of 14,718,100 ha. About 86% of the total land area is covered by hills and high mountains, and the remaining 14% are the flat lands of the Terai. Despite the uniqueness and variety of ecosystems across the ecological regions; the ecosystems, are very fragile and prone to degradation both inherently and in response to anthropogenic activities. A product of young geological and adverse climatic conditions, excessive resource use and associated environmental degradation in the country are responsible for the accelerated rate of natural disasters like soil erosion, land degradation and mass wasting, which in turn are making the ecosystems insubstantial. This review therefore aims to provide information on ecosystem restoration needs and initiatives in Nepal. With the existing natural and anthropogenic disturbances that are prevalent in the ecosystems of every ecological regions of Nepal, ecosystem restoration practices are of immediate need. Similarly, restoration approaches are of prime requisite in the protected areas also. Though started in project level basis and in conjunction with cross-cutting programs, ecosystem restoration interventions are in initial stage in Nepal. In this regard, future ecosystem restoration initiatives should be made successful with intensive efforts, appropriate technology and optimum inputs. It will be necessary to identify the areas requiring restoration, and plan for the implementation of appropriate activities for the successful restoration of degraded ecosystems in each ecological regions of Nepal.